INNOVATION STRATEGY TO ACHIEVE COMPETITIVE ADVANTAGE IN HOTEL KUSUMA AGROWISATA BATU - Try Noviyanti; Desi Tri Kurniawati (Jurnal Ilmiah Mahasiswa FEB, 2012)
This study aims to analyze whether the innovation strategy at Hotel Kusuma Agrowisata Batu can create competitive advantage. The method used in this research  is  qualitative  research.  Data  obtained  by  interview to  the management of Hotel Kusuma Agrowisata Batu  (Internal)  and  via the  internet, books, articles (external), while the data collection method is case study. Analysis tools  used include  analysis of  EFAS,  IFAS  Analysis,  SWOT  Analysis,  and Analysis of  Grand Strategy.  IFAS  and  EFAS  Analysis  results  showed  that the total  value of  the power  is greater than  the total  value of  total  weakness  and opportunity greater than the total  threat.  In the SWOT analysis matrix generated alternative  strategies  SO  Grand Strategy  and  the  analysis  shows  Kusuma Agrowisata  Batu  Hotel  occupies  the first quadrant  position  which  means  an aggressive position. Results of the analysis showed  that the innovation strategies undertaken by Hotel Kusuma Agrowisata Batu is product innovation strategy and managerial innovation. Thus it can be said that a business accommodates Kusuma Agrowisata Batu hospitality services to achieve competitive advantage.Keywords: Strategi Agresif, Strategi Inovasi, Strategi Generik, IFAS, EFAS, Matriks SWOT, Grand Strategy